1972
DOI: 10.1126/science.177.4043.62
|View full text |Cite
|
Sign up to set email alerts
|

11-Hydroxy-Δ 9 -tetrahydrocannabinol: Pharmacology, Disposition, and Metabolism of a Major Metabolite of Marihuana in Man

Abstract: 11-Hydroxy-Delta(9)-tetrahydrocannabinol, administered intravenously to man, produces psychologic and pharmacologic effects that persist for several hours. The drug and its metabolites are excreted in urine and feces for more than 1 week. The pharmacology, disposition, and metabolism of 11-hydroxy-Delta(9)-tetra-hydrocannabinol mimic that of Delta(9)-tetrahydrocannabinol, thus providing evidence that Delta(9)-tetrahydrocannabinol (the major active component of marihuana) is converted to the 11-hydroxy compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(56 citation statements)
references
References 6 publications
(5 reference statements)
2
53
0
1
Order By: Relevance
“…The time profile of the pharmacodynamic effects was more similar to the concentration curve of 11-OH-THC than that of THC. A previous study reported that 11-OH-THC induced a quicker onset of the pharmacodynamic effects compared with THC [34][35][36]. These results in this study are quite promising for a fast onset of the clinical effects in a patient population, although future studies should carefully investigate the relation between pharmacodynamic effects in healthy volunteers and clinical effects in patients.…”
Section: Pharmacodynamicsmentioning
confidence: 56%
See 1 more Smart Citation
“…The time profile of the pharmacodynamic effects was more similar to the concentration curve of 11-OH-THC than that of THC. A previous study reported that 11-OH-THC induced a quicker onset of the pharmacodynamic effects compared with THC [34][35][36]. These results in this study are quite promising for a fast onset of the clinical effects in a patient population, although future studies should carefully investigate the relation between pharmacodynamic effects in healthy volunteers and clinical effects in patients.…”
Section: Pharmacodynamicsmentioning
confidence: 56%
“…Preclinical studies have found 11-OH-THC to be a highly potent CB1-agonist [14,15], and clinical studies also reported more rapid and larger effects after 11-OH-THC administration compared with THC [34][35][36]. In itself, this would have allowed us to predict the pharmacodynamic effects of higher doses in panel II, by reference to the results of other oral THC formulations in the literature which also produce high concentrations of 11-OH-THC.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Delta-9-tetrahydrocannabinol is rapidly metabolized in the liver by the cytochrome P450 system [24]. The active metabolite of delta-9-THC, 11-hydroxy-delta-9-tetrahydrocannabinol (11-OH-THC), is further oxidized to 11-nor-9-carboxy-THC (THC-COOH), the most ubiquitous THC metabolite found in urine [30,31]. Qualitative screens for this inactive metabolite may remain positive for weeks to months, depending on chronicity of marijuana use.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inhaled bioavailability is between 10% in light users, and 23% in heavy users [5]. THC is mainly metabolized in the liver, by cytochrome P450 enzymes such as CYP2C9, CYP2C19 and CYP3A [6,7] which, in turn, is rapidly oxidized to an active metabolite, 11-hydroxy-THC (11-OH-THC) and further to THC-COOH [8]. ________________________________________ The primary metabolite 11-OH-THC is at least as potent as THC, has a similar pharmacokinetic profile, and probably contributes significantly to the effects observed after THC administration whereas THC-COOH is an inactive metabolite [4,9].…”
Section: Introductionmentioning
confidence: 99%